Correlation of Plasma Iron Profile and Intradialytic Hypotension in Hemodialysis Patients - Tisa Rombot; Stella Palar; Pearla Lasut (Universitas Sam Ratulangi, 2023)
Abstract: Intradialytic hypotension (IDH) has been a common complication which should be aware of, in hemodialysis procedure. Its pathogenesis is multifactorial, and severe anemia is considered as one of the most notable risk factors on IDH. This study aimed to evaluate the correlation between plasma iron profile and intradialytic hypotension in hemodialysis patients. This was an analytical and retrospective study using medical records of hemodialysis patients at Prof. Dr. R. D. Kandou Hospital, Manado from January to May 2022. Sampling was conducted through consecutive sampling method, on available records. Patients with CKD grade 5 which undergoes routine HD twice a week for >3 weeks, aged 18-60 years old were included, while subjects with sepsis, malignancy, autoimmune disease, crisis hypertension, and unstable congestive heart failure were excluded for further studies. The details on iron profile and blood pressure measurement were then extracted, which then analyzed with descriptive analysis and Pearson correlation using IBM SPSS Statistics 26.0. The results obtained a total of 35 patients; 57.1% were male. The Pearson correlation analysis on all variables reported several notable significant results, with a correlation between iron profile and blood pressure measurement were seen in TIBC and systole pre- and post-procedure (-.496 and -.611 respectively) with strong negative relationship; and serum ferritin value with systole post-procedure (.373) implying moderate positive relationship. The results suggested that the increase of ferritin value and decrease of TIBC value were correlated with the increase of systole blood pressure. Meanwhile, the TIBC had a strong positive correlation with systolic changes (.473) meanwhile serum iron had a moderate negative correlation with diastolic changes (-.365). In conclusion, there is a significant correlation between iron profile and changes in blood pressure, with higher iron profile value (lower TIBC) is positively correlated with the increase of both systole and diastole measurement; also negatively correlated with the reduction of blood pressure in hemodialysis patients Keywords: iron; ferritin; intradialytic hypotension; hemodialysis; transferrin; total iron binding capacity